Hydroponic Ecoprenaurship Training at AWH Tebuireng Middle School - Manasikana, Oktaffi; Arifah Fitriyah, Lina; Af’idah, Noer; Wahyu Wijayadi, Andri (Universitas Dinamika, 2024)
AWH Tebuireng Jombang Middle School is a boarding school-based school with a superior program of instilling student character. concern for the environment, especially the use of waste in schools and the character of entrepreneurship. This service intends to conduct hydroponic cultivation education at AWH Tebuireng Jombang Middle School. The target of the service is the teachers and students of SMP AWH Tebuireng Jombang. This service aims to provide environmentally oriented waste utilization training based on hydroponic plant entrepreneurship. The method of this activity is delivery of material, discussion and practice. The benefit of this dedication is a means of knowledge and entrepreneurial practice by utilizing environmental preservation. The results obtained in the activity were that students and teachers at SMP AWH Tebuireng Jombang received education and practice about vegetable hydroponic ecopreanaurship by utilizing school waste. Lectures and practices on ecoprenaurship, hydroponic vegetable cultivation, utilization of waste for nutrients and hydroponic growing media, procurement of seeds and seedlings for hydroponic vegetables, management of hydroponic vegetable plants, hydroponic harvesting and sales of hydroponic crops. From the results of the questionnaire, 78% of service participants stated that they wanted to practice ecoprenaurship activities in hydroponic vegetable cultivation.